Condition and value of secondary forest in Laos : an analysis along a gradient of accessibility in Luang Prabang - Puwadej Meknapapong; Schmidt-Vogt, Dietrich; Webb, Edward L.; Shivakoti, Ganesh P.; Messerli, Peter; Thailand (H.M. Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Laos is abundant in forest resources on which a large number of people depend on secondary forests that consitute a considerable share of this resource. Unfortunately the policies related to secondary forest management seem inconsistent with the government's current development strategies and lead to unintentionally negative effects on either forest resources or local livelihood. This research studied the condition and value of secondary forests along a gradient of accessibility since accesibility was considered as a proximate variable for factors affecting forest condition and local livelihood. Three villages on the same road in Luang Prabang province were selected as the study area representing a gradient of accessibility. Relevant data were collected through forest inventory survey, household survey, group discussion, key informant interview, field observation and secondary data. The study findings show that forest condition is worse in the better accessible village where residents have better livelihood and are less dependent on forest resources, whereas forest condition of the remote area is exquisite even though the local people are highly dependent on forest resource. The analysis indicates that accessibility has brought infrastructure, development, government control, agriculture extension and market influence which generates more income, better health care and eventually better livelihood. Unfortunately, on the other hand, it has also stimulated the problems of overpopulation, land scarcity, loss of traditional system, forest overexploitation and ultimately forest degradation. In order to balance forest use and livelihood improvement, the study has suggested agroforestry or integrative plantation for each degree of accessibilty and human resource development by supporting extention and education to reduce pressure on land and forest resource and keep improving accessibility and local livelihood towards sustainable development.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Natural Resource Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Forests and forestry -- Loas -- Luang Prabang